Pelatihan Ecoprint dalam Mendukung Kreativitas Siswa Kelas 5 MI Tarbiyatus Shibyan - Nikmatul Luailiya; Nana Misrochah; Hasna Nurfiani; Aji Masyaid; Dwi Margi Astuti; Esolina Afifah; Sekar Ajeng Pangestika; Titin Komalasari (Jurnal Pengabdian KOLABORATIF, 2024)
Ecoprint is a technique used to beautify fabric by utilizing natural materials. The ecoprint dyeing technique is simple, practical, easy to find materials for, environmentally friendly, and has artistic value. The lush environment of MI Tarbiyatus Shibyan, which is rich in various plants, supports the implementation of ecoprint training activities that can also enhance students' creativity. This activity aims to provide knowledge, train, and guide students in creating ecoprints to enhance their artistic creativity while reducing environmental pollution. The implementation method begins with providing material, training, and guidance in making ecoprints. The result of this activity is enthusiastic students expressing their creativity and imagination through environmentally friendly creations, which can be further developed and utilized to reduce environmental pollution in the surrounding area.